An investigation of back lobe reduction of microstrip patch antenna at 2.4 GHz using slots / Shaiful Azad Mohd Saleh - Mohd Saleh, Shaiful Azad (2016)
This project focuses on the investigation of back lobe reduction using slots at frequency of 2.4 GHz. The investigations were carried out at two different structures. First, slots on the ground plane and second, slots on the patch itself. The microstrip patch antennas were designed on 1.6 mm FR-4 substrate with dielectric constant of 4.3 and loss tangent of 0.025. The back lobe is reduced from -8.958 dB to -9.870 dB but the resonant frequency is shifted from 2.4 GHz in simulation to 2.5 GHz in measurement.